Menghadapi Krisis dengan Kewirausahaan Sosial: Memperkuat Ketahanan Bisnis di Komunitas Rentan Pasca Bencana - Rahmat, Hayatul Khairul (Journal of Current Research in Humanities, Social Sciences, and Business, 2025)
This study examines the role of social entrepreneurship in enhancing business resilience in disaster-prone communities. By leveraging social enterprises, these communities can develop adaptive strategies to recover from economic disruptions caused by disasters. Social entrepreneurship not only addresses immediate needs such as housing, food, and healthcare, but it also fosters long-term sustainable solutions by creating jobs, providing access to resources, and building community capacity. The research identifies the challenges faced by social enterprises, including limited access to resources, markets, and capital. Furthermore, it emphasizes the importance of collaborative efforts between the public, private, and civil sectors in optimizing the impact of social entrepreneurship. This paper concludes by highlighting successful case studies and proposing strategies for integrating social entrepreneurship into disaster resilience frameworks.